Collective Social Actions of Fisherman’s Wife on Anticipating Disaster Technology - Napsiah Napsiah (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2015)
This research reveals the collective social action done by fishermen’s wife to response the existence of Tanjung Adikarto Fishing Port which will launched soon in Karangwuni district, Kulon Progo Regfency. The method used in this research to study the social phenomenon was qualitative. The purposeful sampling was used to determine some informants which were interviewed. Observation was done as to gather secondary data to complement the primary data from informants. The research result showed that the collective social action of the fisherman’s wife was to set up the group to accommodate their aspiration and to increase their bargaining position in the society on economic, social, culture and local politic aspects. The social marginalisation by industrialisation of the fishing port can be eliminated due to their bargaining position more stronger.